ТЕОРЕТИЧЕСКИЕ ПОДХОДЫ К ФОРМИРОВАНИЮ СТРАТЕГИЙ ПСИХОЛОГИЧЕСКОЙ БЕЗОПАСНОСТИ СПОРТСМЕНОВ - Елмуратова, А.У. (SCIENCE and SOCIETY, 2024)
This article will talk about the methods of self-protection, mechanisms of self-regulation and emotional volitional qualities of athletes during their career. Also, theoretical information about the types and forms of psychological protection is presented the role of human behavior in society.
Keywords: psychological protection; willpower; methodology; mexanizm; individual; komponent; adequate; qualification; stability; flexibility; ability; stress; e; extreme; psychotic; consciousness; anxiety; emotional